Structural and Functional Dissection of the 5′ Region of the Notch Gene in Drosophila melanogaster - Volkova, Elena I. (Genes (Basel), 2019)
Notch is a key factor of a signaling cascade which regulates cell differentiation in all multicellular organisms. Numerous investigations have been directed mainly at studying the mechanism of Notch protein action; however, very little is known about the regulation of activity of the gene itself. Here, we provide the results of targeted 5′-end editing of the Drosophila Notch gene in its native environment and genetic and cytological effects of these changes. Using the Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR associated protein 9 (CRISPR/Cas9) system in combination with homologous recombination, we obtained a founder fly stock in which a 4-kb fragment, including the 5′ nontranscribed region, the first exon, and a part of the first intron of Notch, was replaced by an attachment Phage (attP) site. Then, fly lines carrying a set of six deletions within the 5′untranscribed region of the gene were obtained by ΦC31-mediated integration of transgenic constructs. Part of these deletions does not affect gene activity, but their combinations with transgenic construct in the first intron of the gene cause defects in the Notch target tissues. At the polytene chromosome level we defined a DNA segment (~250 bp) in the Notch5′-nontranscribed region which when deleted leads to disappearance of the 3C6/C7 interband and elimination of CTC-Factor (CTCF) and Chromator (CHRIZ) insulator proteins in this region.